The intestinal sutures insufficiency: factors of risk and prognostication, based on genetic investigations - O. Yu. Usenko; Ya. Yu. Voitiv (Клінічна хірургія)
Objective. To improve the results of treatment in patients, suffering insufficiency of sutures of intestinal anastomoses, using analysis of rate in the genes polymorphous variants of the matrix metalloproteinase Type 2 (C-1306 →T) and the tissue inhibitor of the matrix metalloproteinase Type 2 (G303 →A), as well as the result of elaboration of genetic diagnosis and prognostication of such complication.